Pengaruh Kreativitas Mengajar Guru PAI Terhadap Motivasi Belajar Peserta Didik Mata Pelajaran Pendidikan Agama Islam (PAI) Di SDN Se Kecamatan Samarang Garut - Salamudin, Ceceng; Ramdani, Rifki Muhamad (STAI Al-Musaddadiyah Garut, 2023)
Education and character development are crucial aspects of an individual’s life, as character significantly influences one's success. Therefore, it is essential to cultivate strong and positive character traits continuously. One such important trait is humility, known in Islam as